Legalization Of The Sexual Violence Law Perspectives Rule Of Jurisprudence Maslahah Leader Policy - Suryanto, Muhammad Handika; Hamidah, Tutik; Jazil, Syokron (Universitas Widya Gama Malang, 2024)
Cases of sexual violence in Indonesia from year to year are increasing. The government also responded by passing the Law on Sexual Violence in 2022. It aims to ensure protection for Indonesian society, especially women and children, from the threat of sexual violence. But, there is a rule of jurisprudence whose essence is that the policies of the leader must cause benefit to his people. Therefore, this study aims to describe the purpose of establishing and ratifying the Sexual Violence Law and to analyze the benefits of the leader's policy in the passage of the Sexual Violence Law. The research method is descriptive normative by conducting literature studies from the main sources of the Academic Manuscript of the Law on the Crime of Sexual Violence. The results and discussion of this study state that the main content of the formation and ratification of this law is an effort to update a comprehensive legal umbrella that realize protection for society in general and victims of sexual violence in particular. When viewed from the rules of jurisprudence that theoretically the ratification of this law has implemented the policy of a good leader, namely based on the content of the articles in it although rudimentary. However, it practically cannot be categorized as a policy of a good leader because this law has just been passed and has not been implemented in society as a whole and only partially.